Eksplorasi Mikoriza pada Lahan Bekas Tambang Emas Masyarakat di Mandailing Natal - Sahat A. Sihombing; Delvian Delvian; Deni Elfiati (Peronema Forestry Science Journal, 2016)
The mycorrhizal is affected by biotic and abiotic factor. The purpose of this research is to explore the mycorrhizal on the soil of former gold mine community in Mandailing Natal so that we know the types of native mycorrhizal of the area. The data got from this research used to helps land reclamation efforts by the application of mycorrhizal on land mine. This activity will improve the condition of the damaged environment or increase productivity of the land. This research use soil separating method to obtain spores and root coloring method to find out root colonization. Result from this research is 2 genus spores are found they are genus Acaulospora 5 types of spores / 10 g soil and genus Glomus 11 types of spores / 10 g soil. The percentage of mycorrhizal colonization on former gold mine community in  Mandailing Natal is revolve between 8,12% - 28,55% .Key words: Mycorrhizal, genus Acaulospora and genus Glomus, former gold mine land community